Análise da equidade horizontal do gasto por aluno entre redes públicas de educação básica - Fernandes Junior, Rubens Rodrigues (2020)
Given the great complexity of the Brazilian educational system, expressed by the tens of millions of basic education enrollments and distributed in 5,597 educational networks, previous researches have shown the inequality of funding and expenditure per student in different Brazilian locations. Inequality in expenditure per student among the various education networks began to diminish with the implementation of policies aimed at maintaining and developing education in the 1990s. However, inequalities perish due to factors such as different levels of socioeconomic development, infrastructure and tax collection among states. In front of the concept of equity established in the education funding literature, the research aimed to analyze the horizontal equity of expenditure per student in public Brazilian basic education networks. Through the calculation of four inequality measures and some indicators of analysis of expenditure per student, using the information provided by the Brazilian Public Sector Accounting and Tax Information System, the Information System on Public Budgets in Education and the School Census of Basic Education, the methodological procedures compared the inequality of expenditure per student in state and municipal school systems across Brazil, in the years 2006 and 2017. The results revealed that there was a considerable reduction in inequality between and within the states and that there was an increase in the median values of expenditure per student in most of the states analyzed, with emphasis on those that received complementation from the Federal Government in 2017 (AL, AM, BA, CE, MA, PA, PB, PE and PI). The results also showed that there was an increase in the municipalization rate in all states. Fourteen states (AC, AM, BA, CE, ES, MA, PA, PB, PE, PI, PR, RO, RR, SE and PR) were identified with an “acceptable” level of inequality in 2017. However, as is undesirable to have an equal distribution if the expenditure is relatively low, only four states (ES, PR, RO and RR) were considered “acceptable” in the criteria of inequality and level of expenditure per student.